PENGEMBANGAN MEDIA PEMBELAJARAN TAHFIDZUL QUR’AN BERBASIS VIDEO DENGAN METODE TALQIN DALAM MENINGKATKAN HAFALAN AL QUR’AN TINGKAT SEKOLAH DASAR - Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to develop engaging and interactive video media for Quran memorization using the talqin method for elementary school students. The talqin method, which emphasizes listening and imitating the teacher's recitation, has proven effective in strengthening memorization, but its implementation in the classroom still faces challenges such as limited time and the number of teachers. This study used a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results show that the developed video media aligns with the learning characteristics of elementary school students and successfully improves the quality of their memorization in terms of recitation, tajweed, and memory (mutqin). Expert validation and field trials indicate that this media is feasible, practical, and effective as a support for Quran memorization learning in elementary school settings. These findings provide a significant contribution to learning innovation based on the integration of classical methods and digital technology in Islamic education.